P624 Long-term effectiveness of anti-TNF therapy in pediatric-onset inflammatory bowel diseases: a population-based study. (21st January 2022) - Fumery, M; Savoye, G; Ley, D; Dupont, C; Bertrand, V; Spyckerelle, C; Guillon, N; Desreumaux, P; Gower-Rousseau, C; Sarter, H; Turck, D; Leroyer, A
Abstract: Background: Anti-TNFs antibodies are the first biologic treatment option in inflammatory bowel disease (IBD). The long-term effectiveness of this strategy at the population level is poorly known, particularly in pediatric-onset IBD. Methods: All patients diagnosed with Crohn's disease (CD) or ulcerative colitis (UC) before the age of 17 between 1988 and 2011 in a population-based registry were followed retrospectively until 2013. Among patients treated with anti-TNFs, the cumulative probabilities of anti-TNF failure defined by primary failure, loss of response or intolerance were evaluated. Factors associated with anti-TNF failure were investigated by a Cox model. Results: Among a total of 1007 patients with CD (median disease duration, 3.2 years IQR (1.2–7.6) and median follow-up 8.8 years (IQR, 4.6–14.2)) and 337 patients with UC (median disease duration, 2.5 years IQR [1.1–4.5] and median follow-up 7.2 years (IQR, 3.8–13.0)), respectively 481 (48%) and 81 (24%) were treated with anti-TNFs. Median age at anti-TNF initiation was 17.4 years (IQR, 15.1–20.9). Median duration of anti-TNF therapy was 20.4 months (IQR, 6.0–59.9). In CD, the probability of failure of 1 st line anti-TNF therapy at 1, 3 and 5 years was respectively 29.3%, 47.0% and 54.6% for infliximab (n = 397) and 22.6%, 37.7% and 48.0% for adalimumab (n = 83). In UC, the probability of failure of 1 st line anti-TNF therapy at 1, 3 and 5 years was respectively 37.3%, 49.0% and 61.0% for infliximab (n = 71) and 12.5% for these 3 timepoints for adalimumab (n = 10). In CD, probabilities of primary failure, loss of response and intolerance at 5 years were 10.4%, 36.7% and 6.8% (n = 480), respectively; in UC, these same probabilities were 7.5%, 39.2% and 11.3% (n = 81), respectively. Female sex (Hazard Ratio (HR) 1.43, 95% CI 1.09–1.87; p = 0.010) and intestinal resection prior anti-TNF initiation (HR 1.73, 95% CI 1.21–2.47, p = 0.003) were associated with anti-TNF failure in multivariate analysis. Conclusion: In a population-based study of pediatric-onset IBD, approximately half of anti-TNFs users discontinue use within 5 years. Loss of response account for around two-thirds of failure, both for CD and UC.